국내 보리 품종의 전분 관련 특성 평가 - 윤영미(Young-Mi Yoon):김경훈(Kyung-Hoon Kim):강택규(Taek-Gyu Kang):강성욱(Seong-Wook Kang):강혜정(Hye-Jung Kang):강천식(Chon-Sik Kang):김양길(Yang-Kil Kim); 박철수(Chul Soo Park); 조성우(Seong-Woo Cho) (Korean journal of breeding, 2019)
Starch properties of 32 Korean barley cultivars (Hordeum vulgare L.) were evaluated to improve the Korean barley breeding program. The average amylose content of non-waxy barley cultivars was approximately 3.5 times higher than that of waxy barley cultivars. Furthermore, non-waxy barley cultivars showed lower damaged starch content, water retention capacity, swelling volume, swelling power, and peak viscosity than waxy barley cultivars, while they showed bigger average starch granule size and higher final viscosity. Among Korean barley cultivars, the amylose content showed a positive correlation with damaged starch content, water retention capacity, swelling volume and power, and peak viscosity, while showing a negative correlation with pasting temperature and final viscosity. Among non-waxy barley cultivars, the amylose content showed a positive correlation with damaged starch content, but correlation with swelling power, peak viscosity, pasting temperature, and final viscosity was negative. Among waxy barley cultivars, the amylose content showed negative correlation with peak viscosity. There were positive correlations between swelling volume and peak viscosity among Korean barley and waxy barley cultivars. Also, there were positive correlations between swelling power and peak viscosity among Korean barley and non-waxy barley cultivars. Principal Components Analysis revealed that amylose content and peak viscosity are the main factors affecting starch properties of Korean non-waxy barley cultivars, and Korean non-waxy barley cultivars can be classified into two groups with these two factors. Water retention capacity and peak viscosity are the main factors affecting starch properties of waxy barley cultivars and classify them into two groups. The starch properties of Korean barley cultivars demonstrated in this study are useful to improve end-use quality for processed foods using barley. In addition, the continuous qualitative evaluation of barley is very important for the Korean barley breeding program. KCI Citation Count: 2